The Jewish Women at the Union Factory, Auschwitz 1944: Resistance, Courage and Tragedy. Issue 1 (2nd January 2017) - Harran, Ronnen
Abstract : On 5 January 1945, four Jewish female prisoners were executed by hanging in Auschwitz. They were charged with stealing gunpowder from the 'Union' munitions factory, where they were force-labored, and smuggling it to the prisoners of the Sonderkommando at the nearby camp of Birkenau, who mutinied three months earlier, on 7 October 1944. This paper delves into the details surrounding the uprising of the Sonderkommando : it traces the preceding events, namely, the establishment and activity of the underground network for the smuggling of gunpowder, and then it delineates the German investigation following the uprising, which led to the imprisonment and execution of the four Jewish women. This paper presents several main results. First, contrary to common knowledge, the four women who were executed were not alone in the smuggling activity: no less than 30 Jewish female prisoners participated in the gunpowder smuggling, carried out in secrecy during a period of about 7 months. Regarding the investigation that followed the uprising, this paper reexamines two distinct, yet credible narratives concerning the circumstances that led to the arrest of the four women. It determines that both are valid, non-contradictory, but rather complement one another. Perhaps the most important finding is uncovering the reason for which the four women were accused of smuggling gunpowder: camp authorities chose to regard the proven smuggling as an act of sabotage. Thus, these women paid with their lives for the widespread sabotage that was commonplace at the 'Union' factory, which the camp authorities failed to uncover and prevent. The four women were hanged in order to terrorize the laborers at the 'Union', so as to prevent further acts of sabotage, and to demonstrate to higher echelons of the SS and the army that they are determined to put an end to sabotage once and for all.